2016
DOI: 10.1021/acs.jpcc.6b09202
|View full text |Cite
|
Sign up to set email alerts
|

Role of Au(I) Intermediates in the Electrochemical Formation of Highly Anisotropic Gold Nanostructures with Near-IR SERS Applications

Abstract: In the presence of certain stabilizing ligands, such as pyridine derivatives, the reduction of Au(III) ions has been speculated to generate Au(I) intermediates that may play a key role in nanoparticle growth. Herein, the electrochemical behavior of Au(III) in the presence of 4-methoxypyridine, Py, is reported in aqueous electrolytes. Voltammetric analysis reveals that a spontaneously formed Au(III)−Py complex undergoes a two-step reduction process. The first reduction involves the transfer of two electrons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…These crystallographic surfaces of gold support a potential-dependent horizontal to vertical orientation change in adsorbed pyridine, 4-dimethylaminopyridine, and 4-methoxypyridine, and it is somewhat surprising that the surface enhanced vibrational studies described above clearly indicate that the AuNDs used herein provide the expected response of polycrystalline gold rather than that of Au {100} or Au {111} surfaces. Lead underpotential deposition testing of the AuNDs (see Supporting Information) revealed that the extent of low energy crystal faceting on these AuNDs was lower than that previously reported . It is noteworthy that a pulsed potential step rather than a potential sweep and hold was used to make the AuNDs herein, and although the overall morphology as observed by SEM seems remarkably similar, the modified deposition and growth conditions likely make a significant difference to the crystallography of the electrodeposited structures.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…These crystallographic surfaces of gold support a potential-dependent horizontal to vertical orientation change in adsorbed pyridine, 4-dimethylaminopyridine, and 4-methoxypyridine, and it is somewhat surprising that the surface enhanced vibrational studies described above clearly indicate that the AuNDs used herein provide the expected response of polycrystalline gold rather than that of Au {100} or Au {111} surfaces. Lead underpotential deposition testing of the AuNDs (see Supporting Information) revealed that the extent of low energy crystal faceting on these AuNDs was lower than that previously reported . It is noteworthy that a pulsed potential step rather than a potential sweep and hold was used to make the AuNDs herein, and although the overall morphology as observed by SEM seems remarkably similar, the modified deposition and growth conditions likely make a significant difference to the crystallography of the electrodeposited structures.…”
Section: Resultsmentioning
confidence: 80%
“…Previous electrochemical studies have shown that under potential sweep and hold conditions, a stable Au­(I)-MOP complex is formed from an initial two electron reduction of the starting Au­(III) complex . Like other reports of electrodeposition of Au­(I) species, Simon et al showed that nanodaggers are preferentially {111} or (100} textured.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This reaction exemplifies lessons to be learnt from viewing electroless plating and related approaches such as colloidal nanoparticle syntheses [112] from a unified perspective. The fact that DMAP also can be used for electrodepositing anisotropic Au nanostructures further strengthens this point [113] …”
Section: Plating Bath Chemistrymentioning
confidence: 71%
“…The fact that DMAP also can be used for electrodepositing anisotropic Au nanostructures further strengthens this point. [113] Electroless plating contrasts colloidal syntheses in that it does not rely on dedicated capping agents: The deposited nanostructures are growing on surfaces and thus are shielded against aggregation by their immobilization, at least to some extent. One exception is the intermediate case of plating finely dispersed substrates, in which capping agents can be required to prevent clumping.…”
Section: Additivesmentioning
confidence: 99%